Accounting information systems effectiveness: evidence from the nigerian banking sector - Ladan Shagari, Shamsudeen; Abdullah, Akilah; Mat Saat, Rafeah (2017)
Aim/Purpose The purpose of this study is to investigate the interrelationship among the quality measures of information system success, including system quality, information, quality, and service quality, that eventually influence accounting information systems effectiveness. Background It is generally believed that investment in an information system offers opportunities to organizations for business process efficiency and effectiveness. Despite huge investments in accounting information systems, banks in Nigeria have not realized the full potential benefits of using these systems because of persistent failures. Few studies have been conducted to address the problem. Methodology A survey research design was used to collect data, and a total of 287 questionnaires were retrieved from respondents in the Nigerian banking sector. Contribution This study contributes to the understanding of the most important antecedent factors of the quality measures, the interrelationship among the quality measures, and the influence of these measures on the accounting information systems effectiveness. Findings The result of the study revealed that security, ease of use, and efficiency are key features of system quality, while the information quality dimension includes accuracy, timeliness, and completeness. The result of the study further revealed that information quality and system quality have significant influences on accounting information systems effectiveness.Recommendations for Practitioners This study provides practitioners with important measures for evaluation of AIS effectiveness in the context of Nigerian banks.Determinants of AIS Effectiveness 310 Recommendation for Researchers Future researchers may build on the findings of current study to conduct further research in the area of AIS effectiveness in different contexts